2017
DOI: 10.1088/1748-9326/aa6fd0
|View full text |Cite
|
Sign up to set email alerts
|

The cost of cooking a meal. The case of Nyeri County, Kenya

Abstract: Energy for cooking is considered essential in achieving modern energy access. Despite this, almost three billion people worldwide still use solid fuels to meet their cooking needs. To better support practitioners and policy-makers, this paper presents a new model for comparing cooking solutions and its key output metric: the 'levelized cost of cooking a meal' (LCCM). The model is applied to compare several cooking solutions in the case study area of Nyeri County in Kenya. The cooking access targets are connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…In fact, a higher abundance of biomass resources could translate into higher consumption and pollution exposures. In order to improve the quality of cooking and reduce exposure to related air pollution, other technologies are required that improve the efficiency of using biomass, such as clean biomass cooking stoves (Kammila et al 2014, Nerini et al 2017a and improved charcoal kilns (Bailis et al 2013, Iiyama et al 2014. However, even if clean cooking stoves are used for biomass, WHO Air Quality Guidelines are often not met (Pope et al 2017).…”
Section: Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a higher abundance of biomass resources could translate into higher consumption and pollution exposures. In order to improve the quality of cooking and reduce exposure to related air pollution, other technologies are required that improve the efficiency of using biomass, such as clean biomass cooking stoves (Kammila et al 2014, Nerini et al 2017a and improved charcoal kilns (Bailis et al 2013, Iiyama et al 2014. However, even if clean cooking stoves are used for biomass, WHO Air Quality Guidelines are often not met (Pope et al 2017).…”
Section: Solutionsmentioning
confidence: 99%
“…In the context of developing regions, strong synergies between health and climate policies are recognised (Cai et al 2018, Markandya et al 2018, while energy access improvement is showed to have more synergies than trade-offs with most other SDGs, including those on health and climate action (Nerini et al 2017b, Grubler et al 2018, McCollum et al 2018. However, countries in SSA would have to achieve unprecedented rates of progress to obtain universal electricity access (SDG 7) within the coming decades (Rao and Pachauri 2017) and improving the efficiency of biomass energy systems is a cost-effective alternative for reducing forest degradation and HAP in the short term (Smeets et al 2012, Nerini et al 2017a.…”
Section: Introductionmentioning
confidence: 99%
“…Energy is needed to restore water-related ecosystems (Target 6.6, Goal 14-15), sustainably manage irrigation in food systems (Target 2.4), increase water efficiency (Target 6.4, 9.4, 11.b) 26,42 , access and mobilise natural resources to end poverty (Target 1.4), and increase food production (Target 2.3, 2.4) 43, 44 . Lack of access to modern energy services can drive ecosystem loss and degradation (Target 15.2) -for example any deforestation and forest degradation associated with use of fuelwood 45,46 .…”
Section: The Environment and Natural Resourcesmentioning
confidence: 99%
“…Cameron, Pachauri [10] quantified the costs of supporting policies to make universal access to clean cooking affordable in South Asia. Fuso Nerini, Ray [11] compare various cooking solutions on the basis of 'levelized cost of cooking a meal' in Nyeri County, Kenya. Pachauri, Rao [12] use a model to simulate future pathways of clean cooking uptake and the outlook for achieving SDG 7.1 in Guatemala, Honduras and Nicaragua.…”
Section: Introductionmentioning
confidence: 99%